ESG versus corporate financial performance: evidence from East Asian Firms in the industrials sector - Naimy, Viviane (2021)
Given the unsettled ESG-CFP (Environmental, Social, Governance-Corporate Financial Performance) relationship and the scarcity of research covering emerging markets firms and the impact of each of the ESG pillars on CFP while considering the industry sector categories, this paper is pioneer in investigating this relationship for 108 East Asian listed firms operating in the Industrials sector for the period extending from 2011 to 2017. The overall ESG scores together with their components are used to study their impact on CFP while considering accounting (Return on Assets (ROA) and Return on Equity (ROE)), and market measures (Stock Return (RET) and Price-to-Book ratio (PB)). We used panel corrected standard errors to address contemporaneous cross-correlations related to the panel cross-sections. Our findings showed that the ESG-CFP relationship depends on the ESG pillars, the type of CFP measures, and the industry nature. No relationship was detected between ESG and CFP when proxied by accounting measures while a concave relationship with Stock Return and a convex relationship with Price-to-Book ratio were revealed. When ESG pillars were considered separately, a convex relationship was obtained between Environmental and accounting performances and between Governance and Price-to-Book ratio while a concave relationship was depicted between Social and accounting performances. At the industry level, ESG negatively impacted the market performance in the Transportation industry compared to no impact in the Capital Goods industry. Consequently, ESG investment decisions in East Asian firms must be well calibrated and planned out to avoid undesired financial outcomes, while a shift in the mindset of managers toward a better ESG development is necessary to attain short-term gains and sustainable fiscal and social advantages.